The Effect of Benson and Autogenic Relaxation Therapy on Sleep Quality, Blood Pressure and Anxiety of Hypertension Patients - Sutrisno, Sutrisno; Nursalam (Universitas STRADA Indonesia, 2023)
Background: Hypertension increases with age, and causes several signs and symptoms that can interfere with the patient's quality of life, including sleep quality and anxiety. Purpose: This study aims to analyze the effect of Benson and Autogenic therapy on blood pressure, anxiety and sleep quality in patients with hypertension. Methods: This study used Pre-experimental research design with one group pre-test and post-test design. This research was conducted in the working area of ??Pukesmas Balowerti, Kediri City, with a sample of 20 respondents determined by purposive sampling technique. Results: Statistical test it is known that the P value 0.000 < 0.05 on blood pressure reduction, P value 0.001 < 0.05 on sleep quality, P value 0.000 < 0.05 on anxiety levels, it can be concluded that there is an effect of relaxation therapy benson and autogenic to decrease blood pressure, anxiety level and sleep quality of hypertensive patients. Conclusion: Benson and deep autogenic relaxation techniques can be used by someone who is healthy or sick and is a non-pharmacological effort to help reduce muscle tension so that the body becomes comfortable, relaxed, reduces pain and stress intensity, increases pulmonary ventilation and increases blood oxygenation.